Nutritional Status and Associated Factors among 24 to 59 Months old Urban Slum Children of Dhaka City (Journal of Armed Forces Medical College, Bangladesh, 2016)
Introduction: Malnutrition is one of the leading causes of disease in children. Prevention of under nutrition is one of the priority efforts to reduce childhood mortality. About 20% of the population is forced to reside in urban slum due to rapid urbanization. Lack of basic human necessities in the urban slum, adversely affects the nutritional status resulting in poor growth and development of the slum children.Objectives: To assess nutritional status and associated factors among 24 to 59 months old urban slum children of Dhaka city in Bangladesh.Materials and Methods: This cross sectional study was conducted during the period of March 2009 to June 2009 among 24 to 59 months old children of Vashantek slum of Dhaka. A total of 207 children who were available along with their mother during data collection period, were included as the study participants. For data collection face to face interview of the mother was performed and to determine the nutritional status of children anthropometric measurement was carried out.Results: Among the total 207 children, 54.1% were male and 45.9% were female. The mean age± standard deviation of the children was 43.6±11.0 months. As per Z-score of National Centre for Health Statistics (NCHS) reference classification, 45.4% children were underweight, 48.3% were stunted and 28.1% were wasted. Majority of the malnourished children were within 46 months of age. There was a little difference in nutritional status between male and female children. As per immunization schedule, 85.0% of the children completed their immunization. A higher proportion of the underweight children (57.7%) were not exclusively breastfed in comparison to that of the wasted children (42.3%). Moreover, it was revealed that there was a positive association between incomplete immunization and underweight, stunting and wasting (p